2008
DOI: 10.1111/j.1467-9361.2008.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐Regional Migration in Transition Economies: The Case of Poland

Abstract: In this paper, we modify the Harris-Todaro model of migration to incorporate the impact of human capital, housing stock and the availability of publicly provided goods like health care and road provision in order to analyse the determinants of migration in different regions of Poland. We apply the Seemingly Unrelated Regression Equation [SURE] model to investigate the data. Our results show that GDP per capita, unemployment and distance have a strong effect on regional migration in this country. Human capital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…Results across studies reveal some common tendencies although these are not directly comparable across studies due to different regional units, data types, and estimation methods. In a study of interregional migration in Poland, Ghatak et al (2008) used the number of dwellings per thousand inhabitants in the destination region as a proxy for housing characteristics and found that elasticity of migration with respect to housing availability was about 9 percent and it was clearly larger than migration elasticities with respect to labour market characteristics. Andrienko and Guriev (2003) explored internal migration in Russia where the share of privately-owned dwellings was included in regressions.…”
Section: Theoretical Considerations and Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Results across studies reveal some common tendencies although these are not directly comparable across studies due to different regional units, data types, and estimation methods. In a study of interregional migration in Poland, Ghatak et al (2008) used the number of dwellings per thousand inhabitants in the destination region as a proxy for housing characteristics and found that elasticity of migration with respect to housing availability was about 9 percent and it was clearly larger than migration elasticities with respect to labour market characteristics. Andrienko and Guriev (2003) explored internal migration in Russia where the share of privately-owned dwellings was included in regressions.…”
Section: Theoretical Considerations and Empirical Evidencementioning
confidence: 99%
“…These are features of many Central and Eastern European (CEE) transition countries. Interregional mobility in CEE transition countries has been explored to some extent by researchers in empirical studies, for example in the case of Russia (Andrienko and Guriev 2003), the Baltic states, mainly Latvia and Estonia (Hazans 2003), Hungary (Cseres-Gergely 2005, Fidrmuc 2004), the Czech Republic (Fidrmuc 2004, Fidrmuc andHuber 2007), Romania (Ghatak and Silaghi 2007), Poland (Fidrmuc 2004, Ghatak et al 2008) and finally a cross-country study by the World Bank (2007). In these studies the main research interest was the relationship between internal migration and labour market conditions usually proxied by unemployment and wage rates, while some of these studies also took into account the effects of housing market conditions (Hegedus 2004, Cseres-Gergely 2005, Andrienko and Guriev 2003, Ghatak et al 2008.This paper aims to consider more explicitly the impact of housing on interregional mobility.…”
Section: Introductionmentioning
confidence: 99%
“…These might be thought of as non-core variables and constitute, together with the core variables, an extended H-T model. Such extended H-T models have been recently successfully applied to regional migration in countries such as Russia (Andrienko and Guriev 2004) and Poland (Ghatak et al 2008), where in both cases the core and a range of non-core variables were found to be significant.…”
Section: Introductionmentioning
confidence: 99%
“…Home ownership has often been associated with decreased labor mobility (Bloze 2009;Fidrmuc and Huber 2003;Green and Hendershott 2001). In addition, the availability and cost of housing in other regions helps determine internal mobility (Fidrmuc and Huber 2003;Ghatak et al 2007). A fundamental constraint for affordable housing in leading regions is the lack of access to credit and underdeveloped mortgage markets.…”
Section: Access To Housing and Creditmentioning
confidence: 99%